2021
DOI: 10.1111/jocd.14629
|View full text |Cite
|
Sign up to set email alerts
|

Approach to differentiate between hyaluronic acid skin quality boosters and fillers based on their physicochemical properties

Abstract: Background The clinical indications, applications, and effect of the injectable hyaluronic acid range skin quality boosters (SQBs) are different than those of filler products. Material properties are increasingly being discussed for differentiation and in connection with clinical effects and esthetic indications. Aims The aim of this study is to evaluate whether SQB products can be differentiated from filler products by their physicochemical material properties. Material and methods Physicochemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…24 The biophysical properties of the HA-EGF filler indicate that the filler is not a suitable biomaterial for use as a space-filling gel in the dermis, where it is subjected to very low shear forces. According to Kleine et al, 25 skin quality boosters demonstrated lower viscosity and complex viscosity (η* and G′) than dermal fillers which are mainly used for volume augmentation. Since the HA-EGF filler showed similar rheology to the skin quality boosters that are available in the market, 25,26 we recommend that they be made available as skin boosters rather than dermal fillers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The biophysical properties of the HA-EGF filler indicate that the filler is not a suitable biomaterial for use as a space-filling gel in the dermis, where it is subjected to very low shear forces. According to Kleine et al, 25 skin quality boosters demonstrated lower viscosity and complex viscosity (η* and G′) than dermal fillers which are mainly used for volume augmentation. Since the HA-EGF filler showed similar rheology to the skin quality boosters that are available in the market, 25,26 we recommend that they be made available as skin boosters rather than dermal fillers.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kleine et al, 25 skin quality boosters demonstrated lower viscosity and complex viscosity (η* and G′) than dermal fillers which are mainly used for volume augmentation. Since the HA-EGF filler showed similar rheology to the skin quality boosters that are available in the market, 25,26 we recommend that they be made available as skin boosters rather than dermal fillers. As the physicochemical properties depend on the EGF content of the HA-EGF filler, further investigation of the ideal composition is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Skin quality is important to human attractiveness and significantly influences the perception of age, health, and youth across ethnicities [4] . Minimally invasive procedures have revolutionized the treatment paradigm for both facial and body skin rejuvenation and the recent history of cosmetic surgery [5] . In these procedures, the demand for treatments with hyaluronic acid (HA) injectables is constantly on the rise, and a large consensus has been gained worldwide for these products in aesthetic medicine and dermatology [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive procedures have revolutionized the treatment paradigm for both facial and body skin rejuvenation and the recent history of cosmetic surgery [5] . In these procedures, the demand for treatments with hyaluronic acid (HA) injectables is constantly on the rise, and a large consensus has been gained worldwide for these products in aesthetic medicine and dermatology [4][5][6] . This market demand has driven the research and development of new advanced HA formulations for different clinical indications and applications while offering improved safety, effectiveness, and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…HA is a polysaccharide that plays a key role in the structural integrity and hydration of the skin [4] . Thus, HA is a molecule that is strongly involved in aging, and this fact drives the use of HA injectables as HA filler products to correct age-related facial contour abnormalities and rhytides due to its ability to function as a space-occupying device or as a skin booster product to notably improve skin quality by stimulation of the production of several extracellular matrix components [5][6][7] . With a large consensus on HA injectables globally, the demand for treatments with these products increases strongly and continuously in the world [1,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%